EXPLORING THE RELATIONSHIP BETWEEN LEADERSHIP, MOTIVATION, AND COMPETENCE AND EMPLOYEE PERFORMANCE AT STIE STMY MAJALENGKA - Abrar Farhan Sudibyo; Ellin Herlina; Deviari Damalita (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study — This study aims to determine how much influence Leadership, Motivation, Competence on Employee Performance at STIE STMY Majalengka either partially or simultaneouslyResearch method— The type of research is causal comparative research. The sampling technique used is non-probability sampling. The data analysis technique used multiple linear regression analysis. The place of this research is on the STIE STMY Majalengka Campus with a sample of 43 employees from the total populationResult— The results of this study indicate 1. Partially Leadership has a significant effect on employee performance, because the value of tcount > ttable is 2.639 > 2.01669 and the significance value is 0.000 <0.05 then Ho is rejected and Ha is accepted. 2). Partially, motivation has a significant effect on employee performance, because the value of tcount > ttable is 2.547 > 2.01669 and the significance value is 0.002 < 0.05, then Ho is rejected and Ha is accepted. 3). Partially, competence has a significant effect on employee performance, because the value of tcount > ttable is 7.291 > 2.01669 and the significance value is 0.000 <0.05, then Ho is rejected and Ha is accepted. Simultaneously Leadership, Motivation and Competence affect employee performance obtained Fcount of 29.627 while for Ftable 2.82 (obtained from the distribution table with 5%). Because fcount > ftable, which is 29.627 > 2.82, Ho is rejected. Ha is accepted.Conclusion— In conclusion, this causal comparative study found that leadership, motivation, and competence all have a significant effect on employee performance at STIE STMY Majalengka. Additionally, the study found that these three factors simultaneously influence employee performance. These findings suggest that organizations should focus on developing effective leadership, motivating employees, and building their competence in order to improve employee performance. These findings may have practical implications for organizations in terms of how they manage and develop their employees, and social implications for individuals and society as a whole in terms of the importance of these factors in the workplace.